A stable hexaazaoctacene cruciform σ-dimer [data] - Maier, Steffen (Universität, 2022)
Buchwald‐Hartwig coupling of a triisopropylsilyl (TIPS)‐ethynylated dibromo‐N,N'‐dihydrotetraazapentacene with 1,4‐bis(TIPS‐ethynyl)‐2,3‐diaminonap...